2008
DOI: 10.1136/ip.2008.019604
|View full text |Cite
|
Sign up to set email alerts
|

Parental poison prevention practices and their relationship with perceived toxicity: cross-sectional study

Abstract: Parents' perceptions of toxicity of substances were sometimes inaccurate. Perceived toxicity was associated with putting substances away immediately after use for six substances and with safe storage for four substances. The effect of addressing perceptions of toxicity on poison prevention practices requires evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…For example, a study of safety practices by parents of young children showed that medicines are more commonly stored at or above adult eye level and cleaning products below adult eye level, with a substantial proportion stored in unlocked locations. 24 Thus non-medicinal products stored at low levels are likely to be accessible to children at an earlier age, while medicines stored at higher levels will become accessible as children are able to stand well enough to reach and climb. 25 In addition, children may observe parents or older siblings taking medicines, and the development of imitation behaviour around the age of 18-24 months may partly explain the higher risk of medicinal than non-medicinal poisoning in children aged over 2 years, 26 and there is some evidence that increased risks of poisonings from medications may be directly related to prescribed medications for depression.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…For example, a study of safety practices by parents of young children showed that medicines are more commonly stored at or above adult eye level and cleaning products below adult eye level, with a substantial proportion stored in unlocked locations. 24 Thus non-medicinal products stored at low levels are likely to be accessible to children at an earlier age, while medicines stored at higher levels will become accessible as children are able to stand well enough to reach and climb. 25 In addition, children may observe parents or older siblings taking medicines, and the development of imitation behaviour around the age of 18-24 months may partly explain the higher risk of medicinal than non-medicinal poisoning in children aged over 2 years, 26 and there is some evidence that increased risks of poisonings from medications may be directly related to prescribed medications for depression.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Interestingly, although the child-resistant (CR) packaging claims to prevent poisoning, paracetamol -which usually enjoys a CR status internationally -is primarily involved in accidents. Crust formation around the cap, improper closure, and lack of customer counseling [15] may explain the observation.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, more than 50% of the parents incorrectly perceived antibiotics and oral contraceptives as harmful in small quantities and cough medications to be harmful only in large quantities. One in five parents was also unaware of the potential toxicity of iron tablets (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulusal ve uluslararası ça-lışmalarda da benzer olarak en riskli tutum, temizlik ürünlerinin ve ilaçların uygun yükseklikte ve kilitli dolapta bulunmamasıdır. 7,18,19 Framingham Güvenlik Araştırması ile yürütülen bir çalışmada, temizlik ürünlerini şişe, bardak ve kavanozda bulundurma riski düşük-orta, evin çevresinde zehirli bitkilerin olup olmadığının kontrol edilmemesi riski yüksek düzeyde bulunmuştur. 7 Zehirlenme açısından risklerin tümünü sorguladığımızda ço-cukların %44,7'sinin risk taşımadığı saptanmıştır.…”
Section: Discussionunclassified